OHP-023 Vedolizumab treatment for inflammatory bowel disease: clinical practice. (25th February 2017) - Garay, C; Oro, M; Senra, L; Gómez, M; Fernández, A; de Ilarduya, E Martínez; Lizama, N; Gómez, A; Martínez, JJ; Valero, M
Abstract : Background: Vedolizumab is an IgG1 humanised monoclonal antibody directed against α4 β7 integrin, approved for moderate–severe ulcerative colitis (UC) and Crohn's disease (CD) in adults with inadequate/lack of response or intolerance to conventional therapies or to a tumour necrosis factor α (TNFα) antagonist. Purpose: To evaluate the effectiveness and safety of vedolizumab in clinical practice in a medium sized hospital. Material and methods: A retrospective observational study was carried out, which included all patients treated with intravenous vedolizumab from October 2015 to date. Data on demographic and clinical characteristics, indications, posology and duration of treatment, previous and concomitant therapies, adverse events and clinical evolution were collected from the electronic health record and the assisted electronic prescription programme. Effectiveness was defined as clinical improvement, and ineffectiveness as treatment suspension due to lack of response or clinical worsening. Results: 10 patients were included (mean age 47.7 years, 60% women). Indications for use were UC in 7/10 patients (70%) and CD in 3/10 patients (30%). The drug was administered according to the officially approved scheme. The mean number of administered doses was 3.4 (2–5). All patients had previously received infliximab, adalimumab, golimumab or ustekinumab with inadequate response, which placed vedolizumab in the second–fourth line of biological treatment. Concomitant therapies were oral corticosteroids, azathioprine, mesalazine and methotrexate. With regard to adverse events, 1 patient experienced nausea and stomach discomfort, not requiring suspension or modification of therapy. Another patient (who had been splenectomised and suffered from immune thrombocytopenic purpura) experienced septic shock, followed by C difficile infection and disease exacerbation, which led to treatment suspension due to lack of effectiveness. 2 more patients suffered disease exacerbations. Currently, 7 patients continue receiving vedolizumab, showing clinical remission. Conclusion: Vedolizumab is a therapeutic approach for treatment of inflammatory bowel disease in clinical practice in patients with poor response or intolerance to other therapies. It has shown modest effectiveness and a safety profile apparently similar to that of other biological drugs. Available data are still limited, and therefore future prospective studies assessing its suitability in this context will be required. No conflict of interest